Revitalisation of Traditional Settlement Impact on Social and Cultural System Dani Tribe in Jayawijaya District Papua Indonesia - M. Amir Salipu (JURNAL EKOLOGI BIROKRASI, 2015)
Abstract: The processes of buildings and environments arrangement consist of development activities that are technical planning and construction, utilization, conservation, buildings and the environment demolition. Heritage area / building can be defined as the area that has connection with the past life more than 50 years, which may be buildings, settlements or other public facilities that are used collectively. The development progresses that have occurred over two decades ago are often implemented only based on economic considerations and the function of the area. The tendency is to ignore the considerations of tradition and history. The change of social and culture values happen as a global phenomenon which tend to emphasize the value of the economic benefit / financial.Revitalization undertaken by the Ministry of Public Works through the PIU Building Planning and Environment (PBL) in the Papua Traditional Settlement Region in Kampung Waisaput Distric Wamena, Jayawijaya, Papua in 2009, is an attempt to change the place to be used for a more appropriate function. The meaning of appropriate function here is the uses that do not require drastic changes, or just bring minimal impact.How the revitalization impact on the Dani socio-cultural systems will be assessed using Malinowski's theory of functionalism to understand the function of culture to human needs. And the use of the theory of traditional houses is to illustrate how the traditional house shape in one region and culture can be different. If the revitalization can increase the social and cultural value of the occupants, then what steps that need to be considered that are applicable in other activities to improve the quality of development in the traditional societies live.Therefore, this study seeks to give an idea, what the impact of government programs (in this case the traditional neighborhood revitalization by the Ministry of Public Works) to change the culture of the Dani system from the perspective of functionalism and traditional houses theory are. The study of traditional settlements equipped with description and view from architectureal theory as a foundation for the theory of residential areas revitalization in architectural research.Keywords: Social and cultural, government programs, study